ASIS&T annual meeting pre‐conference activities: SIG/USE research symposium context in information behavior research. Issue 3 (13th April 2015) - Xiao, Lu; Kim, Kyung‐Sun; Tang, Rong; Given, Lisa; Agosto, Denise E.; Burnett, Gary; Waugh, Amanda
Abstract : EDITOR'S SUMMARY ASIS&T's Special Interest Group/Information Needs, Seeking and Use (SIG/USE) met during the 2014 Annual Meeting for the group's 14th Annual Research Symposium, focusing on Context in Information Behavior Research . Keynote speaker J. David Johnson set the tone as he encouraged research into the context of information activities outside the usual settings and using varied theoretical perspectives and tools. Attendees also heard 14 lightning talks exploring conceptual and methodological issues. Speakers considered time and emotion as dominant contextual influences in information behavior, the role of information overload and ways diverse contexts affect seeking and providing information. Discussion of research methods encouraged a mixed‐method approach and analytic bracketing and illuminated how study participants create their own information context. During the world café session, tablemates discussed how information context is constructed and evolves, research gaps and available methodologies. The symposium ended with presentation of awards for outstanding research, best paper and poster and for travel to pursue studies. Gary Marchionini was recognized for his outstanding contributions to information behavior research throughout his career.